PENGEMBANGAN DESAIN JARINGAN NIRKABEL UNTUK PENINGKATAN KINERJA DAN SARAN AMONITORING CCTV ONLINE DI BANDARA AHMAD YANI SEMARANG (Information Technology and Telematics, 2014)
AbstractWith the development of information technology, computer netwoking and mobile device makefriction and change patterns of community needs, internet is the biggest factor in the change characterized byincreasingly diverse use of a computer networking.Cctv monitoring system for wireless is a system for aims to simplify officer and scurity in order tosecure the task area and reduce crime which often occurs in public places.Data used in the preparation of this thesis includes primary data and secondary data. The method usedin this research is a field study and literature study. Field studies include interviews and documentation. Whilethe literature study conducted by the research literature relevant to the problem tersebut.Analisis system includeplanning, analysis, design, development and implementation.Kata Kunci :desain jaringan. Monitoring cctv.